c-myc oncogene product expression and prognosis in operable breast cancer. - Locker, A. P. (Nature Publishing Group, 1989)
The 62 kDa protein product of the c-myc oncogene (p62 c-myc) is thought to be involved in the control of normal cellular proliferation and differentiation. We have measured oncoprotein levels using a flow cytometric assay in 141 operable breast cancers and have correlated levels with prognostic variables, patient survival and disease free intervals. High levels of p62 c-myc were associated with well differentiated tumours. There was no correlation with tumour DNA index, lymph node or oestrogen receptor status. C-myc oncoprotein levels were not predictive of patient survival or disease free interval. This relationship of oncoprotein levels with tumour histological grade is in keeping with the suggestion that the c-myc oncogene is important in the control of cellular differentiation. The other findings imply that measurement of c-myc oncoprotein levels does not yield useful prognostic information.